2020
DOI: 10.1590/1980-5918.033.ao09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on patellofemoral pain

Abstract: Introduction: Patellofemoral Pain Syndrome is characterized by retro-patellar and peripatellar pain during squatting, kneeling and running whose intensity can be related to Body Mass Index (BMI). Objective: To evaluate the relationship between overweight, pain and function in women with Patellofemoral Pain Syndrome (PFPS). Method: Cross-sectional observational study of fifty-four women with PFPS assessed in the period between January and December 2015, in the physiotherapy outpatient clinic of a tertiary hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This confirms the finding that being overweight was a risk factor of PFP. However, many studies suggested that height, weight and BMI did not impact pain intensity, or the function in patients with PFP and consequently did not considered as a significant risk factor 25,28,29 . These differences may be due to the previous literature that was limited to a specific gender, age group, and population.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the finding that being overweight was a risk factor of PFP. However, many studies suggested that height, weight and BMI did not impact pain intensity, or the function in patients with PFP and consequently did not considered as a significant risk factor 25,28,29 . These differences may be due to the previous literature that was limited to a specific gender, age group, and population.…”
Section: Discussionmentioning
confidence: 99%
“…Patellofemoral pain syndrome (PFPS) is defined by the presence of anterior knee (retropatellar) pain, related to the increase of contact pressure (stress) in the patellofemoral joint, being the most common athlete's knee problem, especially in runners. PFPS etiology is not well established, nevertheless, it's related to multifactorial causes like direct trauma or any activity that may cause patellofemoral joint compression, like long periods of sitting, squatting, going up and down stairs, which makes it harder to diagnose [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…PFPS also makes up 3% of all diseases that attack the knee 1,4 . PFPS risk factors include quadriceps muscle weakness and biomechanical misalignments in the Q angle, tibiofemoral angle, external static rotation of the knee, tibial lateral torsion and hyperpronation of the foot, which affect the distribution of forces acting on the knee joint, since their adequate alignment is necessary for a harmonious functioning between the hip and knee joints [1][2][3]5 . The proximal portion of the femur is influenced by both the frontal and axial plane.…”
Section: Introductionmentioning
confidence: 99%